EFFECTS OF STRAIN RATE AND TEMPERATURE ON THE MECHANICAL PROPERTIES OF GFRP COMPOSITES - Coelho, J. L. V.; Reis, J. M. L. (Revista de Engenharia Térmica, 2011)
In this work, the mechanical response of a composite material based on glass fibers embedded in an epoxy resin was experimentally studied as a function of strain rate and temperature. It was shown that for the temperature range from 23 to 100 °C the elastic properties of the composite are significant affected and the strain rate influences only the ultimate strength. The experimental research data and the approaches presented in this work should significantly extend our knowledge of the effect of elevated temperatures on the mechanical behavior of high temperature polymer matrix composites.